# Cosx=cotx(secx)

## Simple and best practice solution for Cosx=cotx(secx) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Cosx=cotx(secx) equation:

Simplifying
Cosx = cotx(secx)
Multiply cotx * cesx
osxC = c2eostx2
Solving
osxC = c2eostx2
Solving for variable 'o'.
Move all terms containing o to the left, all other terms to the right.
Add '-1c2eostx2' to each side of the equation.
-1c2eostx2 + osxC = c2eostx2 + -1c2eostx2
Combine like terms: c2eostx2 + -1c2eostx2 = 0
-1c2eostx2 + osxC = 0
Factor out the Greatest Common Factor (GCF), 'osx'.
osx(-1c2etx + C) = 0
Subproblem 1Set the factor 'osx' equal to zero and attempt to solve:
Simplifying
osx = 0
Solving
osx = 0
Move all terms containing o to the left, all other terms to the right.
Simplifying
osx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1c2etx + C)' equal to zero and attempt to solve:
Simplifying
-1c2etx + C = 0
Reorder the terms:
C + -1c2etx = 0
Solving
C + -1c2etx = 0
Move all terms containing o to the left, all other terms to the right.
Add '-1C' to each side of the equation.
C + -1C + -1c2etx = 0 + -1C
Combine like terms: C + -1C = 0
0 + -1c2etx = 0 + -1C
-1c2etx = 0 + -1C
Remove the zero:
-1c2etx = -1C
Add 'c2etx' to each side of the equation.
-1c2etx + c2etx = -1C + c2etx
Combine like terms: -1c2etx + c2etx = 0
0 = -1C + c2etx
Simplifying
0 = -1C + c2etx
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`